2018
DOI: 10.1371/journal.pone.0199120
|View full text |Cite
|
Sign up to set email alerts
|

Different effects of propofol and dexmedetomidine sedation on electroencephalogram patterns: Wakefulness, moderate sedation, deep sedation and recovery

Abstract: Sedation induces changes in electroencephalography (EEG) dynamics. However, the distinct EEG dynamic characteristics at comparable sedation levels have not been well studied, resulting in potential interpretation errors in EEG monitoring during sedation. We aimed to analyze the EEG dynamics of dexmedetomidine and propofol at comparable sedation levels and to explore EEG changes with increased sedation levels for each agent. We measured the Bispectral Index (BIS) and 20-channel EEG under dexmedetomidine and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 57 publications
5
27
0
1
Order By: Relevance
“…Changes in the EEG background rhythm and EEG reactivity with an increasing level of sedation were also demonstrated in previous reports [12,31]. In our study, sedation alone significantly influenced the EEG background and reactivity, and the EEG background score and reactivity did not predict mortality if EEG was performed in sedated patients but predicted mortality in non-sedated patients.…”
Section: Discussionsupporting
confidence: 85%
“…Changes in the EEG background rhythm and EEG reactivity with an increasing level of sedation were also demonstrated in previous reports [12,31]. In our study, sedation alone significantly influenced the EEG background and reactivity, and the EEG background score and reactivity did not predict mortality if EEG was performed in sedated patients but predicted mortality in non-sedated patients.…”
Section: Discussionsupporting
confidence: 85%
“…It has recently been reported that BIS values are dependent on the variable EEG spectrums observed with specific sedative agents. 12 Rampil et al 27 reported that BIS monitoring was insufficiently sensitive to assess the level of sedation during nitrous oxide administration. The reliability and applicability of BIS monitoring used to guide propofol sedation has previously been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine has been widely used as a sedative for patients undergoing regional anaesthesia because it prolongs the effect of regional anaesthesia and provides arousable sedation with less effects on respiration . The conventional infusion method for dexmedetomidine is zero‐order infusion which is administered as a maintenance infusion of 0.2‐1 µg kg −1 h −1 after a loading dose of 0.5‐1 µg kg −1 h −1 for 10 minutes . However, the conventional infusion process is entirely the clinicians' decision and it is hard to predict the effect of the infusion dose of dexmedetomidine.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…1 The conventional infusion method for dexmedetomidine is zero-order infusion which is administered as a maintenance infusion of 0.2-1 µg kg −1 h −1 after a loading dose of 0.5-1 µg kg −1 h −1 for 10 minutes. 2,3 However, the conventional infusion process is entirely the clinicians' decision and it is hard to predict the effect of the infusion dose of dexmedetomidine.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%